2019
DOI: 10.1016/j.metabol.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal gene and protein expression increase in response to a high-lipid challenge in human skeletal muscle

Abstract: Peroxisomes are essential for lipid metabolism and disruption of liver peroxisomal function results in neonatal death. Little is known about how peroxisomal content and activity respond to changes in the lipid environment in human skeletal muscle (HSkM). Aims: We hypothesized and tested that increased peroxisomal gene/protein expression and functionality occur in HSkM as an adaptive response to lipid oversupply. Materials and methods: HSkM biopsies, derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…We also reported that acute low-intensity exercise induces a rapid, short-term increase in peroxisomal lipid oxidation (19). Additionally, peroxisomal oxidative capacity increases in response to lipid-rich environments in rodent and human muscle (31,64). Data herein extend upon these findings as they are the first to report that vigorous-intensity exercise training increases peroxisomal oxidation in mice fed a low-fat diet; however, while being fed a lipid-rich NPKD, exercise training further induced several peroxisomal genes and proteins in skeletal muscle.…”
Section: Discussionmentioning
confidence: 78%
“…We also reported that acute low-intensity exercise induces a rapid, short-term increase in peroxisomal lipid oxidation (19). Additionally, peroxisomal oxidative capacity increases in response to lipid-rich environments in rodent and human muscle (31,64). Data herein extend upon these findings as they are the first to report that vigorous-intensity exercise training increases peroxisomal oxidation in mice fed a low-fat diet; however, while being fed a lipid-rich NPKD, exercise training further induced several peroxisomal genes and proteins in skeletal muscle.…”
Section: Discussionmentioning
confidence: 78%
“…It has been further suggested that these tissues upregulate PGC-1α in response to increased lipid intake, acting as a compensatory mechanism for high fat diets and metabolic dysregulation. This co-regulation of peroxisomal and mitochondrial biogenesis has been established in brown adipose tissue, liver and skeletal muscle ( Huang et al, 2017 , 2019 ; Hevener et al, 2020 ). Work has yet to be done showing the proliferation of peroxisomes in cardiac tissue, but findings in other tissues is highly suggestive of the need for future research in this area.…”
Section: Mitochondrial Biogenesis and Dynamicsmentioning
confidence: 85%
“…Under such experimental conditions, peroxisomal localization of ADHAPR might be regulated by accelerating targeting of ADHAPR to peroxisomes and/or by suppressing ADHAPR degradation in peroxisomes. In this context, it is interesting that transcription of mRNAs encoding PMPs including Pex19p is acutely up-regulated in human skeletal muscle at 4 h post-supplementation of high fat meal ( Huang et al, 2019 ). Moreover, ADHARP is highly expressed in several tissues including liver, white adipocytes, and brain ( Lodhi et al, 2012 ), suggesting that acyl-DHAP pathway is involved in the synthesis of non-ether glycerophospholipids.…”
Section: Discussionmentioning
confidence: 99%